Optical cooling and trapping of highly magnetic atoms: the benefits of a spontaneous spin polarization. (7th March 2017) - Dreon, Davide; Sidorenkov, Leonid A; Bouazza, Chayma; Maineult, Wilfried; Dalibard, Jean; Nascimbene, Sylvain
Abstract: From the study of long-range-interacting systems to the simulation of gauge fields, open-shell lanthanide atoms with their large magnetic moment and narrow optical transitions open novel directions in the field of ultracold quantum gases. As for other atomic species, the magneto-optical trap (MOT) is the working horse of experiments but its operation is challenging, due to the large electronic spin of the atoms. Here we present an experimental study of narrow-line dysprosium MOTs. We show that the combination of radiation pressure and gravitational forces leads to a spontaneous polarization of the electronic spin. The spin composition is measured using a Stern–Gerlach separation of spin levels, revealing that the gas becomes almost fully spin-polarized for large laser frequency detunings. In this regime, we reach the optimal operation of the MOT, with samples of typically 3 × 10 8 atoms at a temperature of 15 μ K. The spin polarization reduces the complexity of the radiative cooling description, which allows for a simple model accounting for our measurements. We also measure the rate of density-dependent atom losses, finding good agreement with a model based on light-induced Van der Waals forces. A minimal two-body loss rate β ∼ 2 × 10 − 11 cm 3 s –1 is reached in the spin-polarized regime. Our results constitute a benchmark for the experimental study of ultracold gases of magnetic lanthanide atoms.